The Impact of Digital Skills Training on Increasing the Competitiveness of Educators - Idam Mustofa; Meredith Tandon; Bouyea Jonathan; Eduard Yohannis Tamaela (Journal Emerging Technologies in Education, 2024)
Background:Digital skills training to increase the competitiveness of teaching staff is related to the development of digital pedagogical skills that are relevant to 21st century learning. Digital skills training can be provided to educational staff, such as teachers and lecturers, through vocational education programs and digital skills courses. Research purposes:This research was conducted with the aim of finding out how much impact digital skills training has on increasing the competitiveness of teaching staff to find out and analyze how digital skills training affects the competence and competitiveness of teaching staff in the digital era. This research aims to support the development of relevant and effective digital skills training programs to improve the competence of teaching staff, so that they can help create a workforce that is ready to face the challenges of the digital economy. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From the research results, it can be seen thatDigital skills training is one way to increase the competitiveness of teaching staff. To increase the competitiveness of teaching staff, it shows that this training can influence the competency and competitiveness of teaching staff in the digital era. Digital skills training can help educators develop relevant digital pedagogical skills, which will help them adapt to increasingly sophisticated learning needs and integrate digital technologies in teaching. Conclusion:Digital skills training can help educators develop digital pedagogical skills that are relevant to twenty-first century learning. This will help them adapt to increasingly sophisticated learning needs and integrate digital technology in teaching.